Aplikasi Analytical Hierarchy Process (AHP) pada Pemilihan Software Manajemen Proyek - Komsiyah, Siti (Bina Nusantara University, 2014)
The problem with many alternative decisions in the areas of management and administration commonly referred to as multi-attribute decision problems. For example, the decision problem with many variables so that the target decision can not always be determined easily. Well-known method of approach, to overcome this kind of problem is called the Analytical Hierarchy Process (AHP). AHP technique is given by arranging alternative levels of decision, so as to provide a structured quantitative description. Application of multi-attribute types ofproblems such as problems in the selection of software, car, project proposal, the university, the best employees, and so forth. In this paper, the approach developed using the AHP in software selection project management.